Young teachers’ professional identity in the conditions of social, labor, and digital transformation of Russian society - Vladimirovich Lubsky, Anatoly (2021)
In society, there is a perception of young teachers as the future of the Russian education system who need constant patronage due to their lack of professional experience and skill. However, young teachers present not only a professional resource for the future of Russian education but also a social group with its own interests and values that is able to make a significant contribution to the development of general education in the present. Study proposes a multidimensional methodological construct of the sociological study of the professional identity of young teachers in Russian society developed within the “soft conception” of identity with consideration of both Russian and foreign theoretical and methodological experience. The internal and external factors for the formation of young teachers’ professional identity, as well as the structure, functions, and the real and ideal types of this identity are identified. The detection of tendencies in the development of real professional identity allows identifying the direction of the transformation of young teachers’ professional identity in Russian society via the comparison with ideal types.